TWO-STAGE DYNAMIC TRACKER FOR TRACEBILITY OF THE MOVING OBJECTS - Семко, Олексій; Винничук, Динис (SWorldJournal, 2025)
Object tracking in video is a challenging task in computer vision (CV). At the same time, there are a number of problems that complicate accurate and reliable tracking of objects in video streams, namely: occlusion (overlapping objects, changes in the ap